Effects of annealing temperature on the structure and properties of the LaY2Ni10Mn0.5 hydrogen storage alloy. (1st June 2017) - Xiong, Wei; Yan, Huizhong; Wang, Li; Zhao, Xin; Li, Jin; Li, Baoquan; Wang, Yan
Abstract: The effects of annealing at 1123, 1148, 1173 and 1198 K for 16 h on the structure and properties of the LaY2 Ni10 Mn0.5 hydrogen storage alloy as the active material of the negative electrode in nickel–metal hydride (Ni–MH) batteries were systematically investigated by X-ray diffraction (XRD), scanning electron microscopy linked with an energy dispersive X-ray spectrometer (SEM–EDS), pressure-composition isotherms (PCI) and electrochemical measurements. The quenched and annealed LaY2 Ni10 Mn0.5 alloys primarily consist of Ce2 Ni7 - (2H) and Gd2 Co7 -type (3R) phases. The homogeneity of the composition and plateau characteristics of the annealed alloys are significantly improved, and the lattice strain is effectively reduced. The alloys annealed at 1148 K and 1173 K have distinctly greater hydrogen storage amounts, 1.49 wt% (corresponding to 399 mAh g −1 in equivalent electrochemical units) and 1.48 wt%, respectively, than the quenched alloy (1.25 wt%, corresponding to 335 mAh g −1 in equivalent electrochemical units). The alloys annealed at 1148 K and 1173 K have relatively good activation capabilities. The annealing treatment slightly decreases the discharge potentials of the alloy electrodes but markedly increases their discharge capacity. The maximum discharge capacities of the annealed alloy electrodes (372–391 mAh g −1 ) are greater than the extreme capacity of the LaNi5 -type alloy (370 mAh g −1 ). The cycling stability of the annealed alloy electrodes was improved. Graphical abstract: Highlights: LaY2 Ni10 Mn0.5 alloy belongs to a system of new hydrogen storage materials. Capacity of annealed LaY2 Ni10 Mn0.5 alloy exceeds theoretical capacity of LaNi5 alloy. The annealed LaY2 Ni10 Mn0.5 alloy shows fairly acceptable cyclic durability.